ZOOPLANKTON DIVERSITY OF THE LOWER RIVER NIGER AT AGENEBODE, EDO STATE. NIGERIA. - ADENIYI, A. O; AKINWOLE, A. O.; ABIODUN-SOLANKE, A.O.; OSHOKE , J.O. (Nigerian Journal of Fisheries, 2020)
ABSTRACT The Zooplankton diversity of the Lower River Niger at Agenebode town in Edo State was assessed. The river was stratified into three zones; downstream (DNS), midstream (MDS) and upstream (UPS) based on the hydrological features. Plankton samples were collected using a plankton net of 76μm mesh size with a mouth diameter of 12.50cm. Samples were analyzed using the drop-count method under the light microscope. A total of 2,897 zooplanktons were recorded belonging to 3orders, 10families, 13genera and 20 species, with order: copepod (1605, 55.40%) dominating in abundance. The family: Cyclopidae had the highest number of species (55.06%) of the total zooplankton while Brachionus falcatus falcatus was the most abundant species. Spatially, the DNS had the highest zooplankton abundance (1054, 36.38%) while MDS (890, 30.72%) had the least. There was no significant difference in zooplankton abundance amongst the sampling zones, however, there was a significant difference between DNS and the other two zones. There was a significant difference seasonally in the distribution and abundance of zooplankton obtained in the Lower River Niger at Agenebode. Zooplankton abundance in the wet season was higher than in the dry season with August recording the highest number of 496 species. The zooplankton assemblage of Lower River Niger belongs to three major taxonomic groups, Cladocera, Copepoda, and Rotifera, however, it was dominated by the copepods.